Studying the ability of using no-fines concrete in lightweight structures - Taher, Rabah Basheer Mohammed (Al-Mukhtar Journal of Sciences, 2009)
This paper studies the properties of a lightweight concrete made by canceling the fine aggregate (i.e. no-fines concrete) to use it as a lightweight structural concrete where it is exposed to low compressive stresses and as pervious concrete pavement. Three groups of concrete mixes were made (18 mixes for each group) using three sizes of coarse aggregate (10 mm , 15 mm and 20 mm) taken from Hussein valley which is located to the east of Derna. In each group it was used (3) different weights of cement and (5) different water: cement ratios. The density, percentage of absorption and the compressive strength of the no-fines concrete was determined. The results of tests lead the following conclusions: 1- The no-fines concrete made as a low density varies between (1573.3-1777.8) kg/m3. 2- The maximum compressive strength obtained was (9.1) N/mm2 by using (10) mm size of aggregate, (250) kg of cement and water: cement ratio of (0.45). 3- Increasing the amount of cement in the concrete mixes from (150) kg to (250) kg leads an increase in compressive strength of concrete by (72-128)% and an increase of density by (1.5-6.7)% depending on the aggregate size. 4- There is an optimum water:cement ratio which gives a maximum compressive strength. Any increase or decrease in this ratio lowers the compressive strength. 5- The compressive strength of the no-fines concrete has a direct relationship with the density. 6- The no-fines concrete possesses large voids and more void ratio therefore; it possesses more thermal and sound isolation than the ordinary concrete and allows water to seep through it. 7- The no- fine concrete is more economical than the ordinary concrete as it consumes fewer quantities of cement and aggregate. According to these conclusions, it was reached to a recommendation to use the no- fines concrete instead of the ordinary concrete in lightweight structures and as a pervious concrete pavement in low speed roadways, parking lots, sidewalks, greenhouse floors.